Pengaruh Model Pembelajaran Kooperatif dan Gaya Berpikir Terhadap Hasil Belajar Qira’ah - Sayyidi, Khambali Khadori (Al Mah?ra: Jurnal Pendidikan Bahasa Arab, 2018)
Abstract The objective of this research was to investigate comprehensively the effect of learning model and student’s thinking style on the Arabic reading achievement of the second semester student of the Arabic Education Program, the Faculty of Language and Arts, University of State Jakarta, academic year 2016/2017. This was an experimental research using a two-factor ANOVA at 0,05 and 0,01 significance level. The data was collected using the Arabic reading test and thinking style questionaire. The findings above led to a conclusion that generally cooperatif of MM was more effective implemented than cooperatif of NHT in Arabic reading achievement. Moreover, the students’ thinking style affected their Arabic reading achievement as well. Keywords : Arabic Reading Achievement, Cooperative Learning, Thinking.